Changing the tune: listeners like music that expresses a contrasting emotion - Schellenberg, E. Glenn; Corrigall, Kathleen; Ladinig, Olivia; Huron, David (My University, 2012)
Theories of esthetic appreciation propose that (1) a stimulus is liked because it is expected or familiar, (2) a stimulus is liked most when it is neither too familiar nor too novel, or (3) a novel stimulus is liked because it elicits an intensified emotional response. We tested the third hypothesis by examining liking for music as a function of whether the emotion it expressed contrasted with the emotion expressed by music heard previously. Stimuli were 30-s happy- or sad-sounding excerpts from recordings of classical piano music. On each trial, listeners heard a different excerpt and made liking and emotion-intensity ratings. The emotional character of consecutive excerpts was repeated with varying frequencies, followed by an excerpt that expressed a contrasting emotion. As the number of presentations of the background emotion increased, liking and intensity ratings became lower compared to those for the contrasting emotion. Consequently, when the emotional character of the music was relatively novel, listeners’ responses intensified and their appreciation increased.
Keywords: music; emotion; liking music; music preferences; contrast effect; hedonic ratings